Create Web Charts with jqPlot - Nelli, Fabio; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
Create Web Charts with jqPlotshows how to convert your data into eye-catching, innovative, animated, and highly interactive browser-based charts. This book is suitable for developers of all experience levels and needs: for those who love fast and effective solutions, you can use the jqPlot library to generate charts with amazing effects and animations using only a few lines of code. By the end of the book, you will have a good knowledge of all the elements needed to manage data from every possible source, from high-end scientific instruments to Arduino boards, from simple HTML tables to structured JSON files, and from Matlab calculations to reports in Excel. You will be able to provide cutting-edge charts exploiting the growing power of modern browsers. This book contains content previously published in Beginning JavaScript Charts. Create all kinds of charts using the latest technologies available on browsers Full of step-by-step examples, Create Web Charts with jqPlot introduces you gradually to all aspects of chart development, from the data source to the choice of which solution to apply. This book provides a number of tools that can be the starting point for any project requiring graphical representations of data, whether using commercial libraries or your own.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems